Saudi Novel: Commencements, Efforts, and Headway (5): 'Salma' of Ghazi Al-Gosaibi as an Epitome - Yahya Saleh Hasan Dahami (ELS Journal on Interdisciplinary Studies in Humanities, 2024)
This study explores the evolution of the Saudi novel, highlighting the aesthetic advancements achieved at each stage of its development. By tracing the growth and significance of Saudi narratives, the research underscores the literary contributions of the esteemed novelist Ghazi Al-Gosaibi. Utilizing an analytical-critical-descriptive method, the study addresses key literary issues pertinent to the Saudi novel. It begins with an examination of the novel as a concept and its broader significance in literature, setting the stage for understanding its adaptation and transformation within Saudi Arabia's unique cultural and historical context. This foundational overview is crucial for appreciating the subsequent discussion on the specific developments within Saudi literature, particularly as they relate to the broader trends in global literary practices. The main focus of the study is Ghazi Al-Gosaibi's "Salma," a work that epitomizes the Saudi novel's journey towards literary maturity. Through a detailed examination of "Salma," the research delves into the narrative techniques, thematic concerns, and stylistic choices that characterize Al-Gosaibi's writing. This analysis not only showcases Al-Gosaibi's contribution to Saudi literature but also illustrates the novel's role in reflecting and shaping societal values and cultural identity. The study concludes with a discussion that synthesizes the insights gained, emphasizing the novel's significance as a literary form in Saudi Arabia and its potential for future scholarly exploration.